Integrated monitoring system based on service-oriented IOT architecture in open step-nc environment - Iliyas Ahmad, Maznah (2021)
One of the essential criteria for smart factories specifically the Open CNC machine tool, is bridging the gap between physical machine tool and software applications. The difficulties in this issue were the lack of efficient and sufficient monitoring systems that provide a solution for data acquisition, response, and feedback in real-time. In this study, a methodology to develop an integrated monitoring system to enable data acquisition, response, and feedback-based service-oriented internet of things architecture in STEP-NC based open CNC was proposed. The architecture comprises four main layers, perception, communication, application and CNC machine. The completed system was then tested through two case studies. The first case study is based on STEP-NC Example 1 of Part 21while case study two was based on modified STEP-NC Example 1 of Part 21. Both case studies are tested using a new and worn cutting tool. Based on the conducted case studies, the findings were summarized into four: First, the developed system successfully enabled data flow, from CNC machine tool back to CNC machine, via an integrated monitoring system based service-oriented IoT architecture in STEP-NC Open CNC environment. Secondly, the reading of temperature, vibration and electric current monitoring is higher for the worn cutting tool than the new cutting tool. Third, the percentage different between new and worn cutting tools for temperature is up to 3.38 % and for vibration, it is up to 78.93 %. Fourth, electric current reading is proportional to cutting force as the reading of electric current on cutting insert is higher than reading before cutting tool insert with percentage differences more than 8.33% up to 20%. The case studies summarized that the developed integrated monitoring system is feasible and highly sensitive to any changes, specifically on the cutting tool condition. In the future, this integrated monitoring system could be applied to other Open CNC machine-based plug and play.